Analyzing Hotel Innovation Behavior in the Balaton Region of Hungary to Identify Best Practices - Gyurácz-Németh, Petra; Horn, Nikolett; Friedrich, Nóra (Naše gospodarstvo/Our economy, 2016)
The goal of the research is to investigate the hotel innovation behavior in one of the most important tourism regions of Hungary. The Lake Balaton Region is a very popular area of the country with quite a short season (from the middle of June to August 20). The region is the second most visited area based on the number of guests and guest nights in Hungary. The topic of innovation plays a growing role in the Hungarian hotel sector as well, because competition is very high and keeping guests and employees can be a great challenge. The study involved both qualitative and quantitative research. The qualitative research aimed to identify the best practices of the Hotel Európa Fit****superior which introduced an “innovation by inspiring” strategy and applies several types of innovation in a highly recommended way. The respondents of the questionnaire included 28 hotel general managers (52% of the 54-person sample). The results showed a strong relationship between the type of the hotel and the number of innovations as well as the type of the hotel and the frequency of innovation.